Prevalence of group B streptococcus colonization in pregnant women in a tertiary care center in Korea - Da Hyun Kim; Byoung Jin Min; Eun Jung Jung; Jung Mi Byun; Dae Hoon Jeong; Kyung Bok Lee; Moon Su Sung; Ki Tae Kim; Young Nam Kim (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveThe purpose of this study was to evaluate the group B streptococcus (GBS) colonization rate in pregnant Korean women using selective culture media for GBS and to identify obstetrical complications and GBS-induced early-onset neonatal sepsis.MethodsWe evaluated 1,014 pregnant women who delivered at Busan Paik Hospital between January 2015 and December 2016. GBS colonization was assessed using chromID Strepto B agar. We evaluated GBS colonization in pregnant women, as well as the obstetrical complication and GBS-induced neonatal sepsis rates.ResultsThe total GBS colonization rate was 11.6% (117/1,014). No significant increase was observed in the rate of pregnancy-related complications between the GBS-positive and the GBS-negative groups. Among the 134 neonates born to colonized mothers, early neonatal sepsis was reported in 2 neonates (1.5%); however, these were cases of non-GBS-induced sepsis.ConclusionThe GBS colonization rate (using selective culture media) in this study involving pregnant Korean women showed a higher colonization rate than that previously reported in Korea. Therefore, based on this study, we recommend GBS screening and the administration of intrapartum antibiotic prophylaxis in pregnant Korean women.